Effect of Flaxseed on TGF-Β, IL-6, and MMP9 Genes Expression during Wound Healing Process in Rabbits - Al-Ahmad, Basma Ezzat Mustafa; Mustafa, Nazih Shaban; Mokhtar, Khairani Idah; Lestari, Widya; Sha’ban, Munirah; Nazri, Aliah Ahmad; Jabbar, Omar Abdul (Open Access Macedonian Journal of Medical Sciences, 2023)
BACKGROUND: Wound healing is a natural restorative response to tissue injury, and it involves regulated order of cellular and biochemical actions to reinstate tissue after injury, which involves resurfacing reconstitution, and restoration of tensile strength of injured skin. Normal and impaired wound healing post-significant problems related to healthcare and expenditure. Most of the chemical medications which widely used for wound healing might cause unwanted side effects with prolonged use such as hyper scarring, thus studies using natural products are now deemed important. Flaxseed is a natural product that enhances the immune system functioning against different diseases. Nevertheless, limited studies have been done looking into the response triggered by immune cells and the wound-healing-related genes with the use of flaxseed extract onto the wounded skin for the healing process. AIM: The main objective of this study is to analyze the expression of wound healing-related genes during different stages of the wound healing process induced by flaxseed in vivo. METHODS: The effect of flaxseed oil in the early stages (day 4 and 7) and late stages (day 14) of wound healing was explored on New Zealand white rabbits by creating a longitudinal full thickness wound on their back. The gene expression profiles of transforming growth factor-beta (TGF-β), IL-6, and metalloproteinase (MMP9) genes which have roles in wound healing through inflammation, proliferation, and remodeling were studied by polymerase chain reaction method. RESULTS: Flaxseed extract has significant effects in up-regulating anti-inflammatory marker TGF-β in wounds. Flaxseed oil also reduces the expression level of MMP9 on day 14 of wound healing. CONCLUSIONS: This suggests that flaxseed extract has the potential to promote wound healing through the regulation of TGF-β and MMP9 in vivo.